KONSUMSI APEL MERAH MEMPENGARUHI PERUBAHAN TINGKAT DEMENSIA PADA LANSIA DI RT 05 RW 03 KELURAHAN WONOKROMO - Ernawati, Ernawati; Wijayanti, Lono (Jurnal Ilmiah Kesehatan, 2014)
Dementia to elder is abnormality which can be prevented by consuming red apple. Therefore, this research was purposed to find out the influence of red apple consumption to elder dementia level at Wonokromo RT 05 RW 03. The research used quasi-experiment design, where the population involved 20 elders who got dementia symptom. All populations were taken as the sample using total sampling technique. 8 people were taken as experiment grup and 12 people as control group. The independent variable was red apple consumption whereas the dependent one was dementia level. Moreover, the data collected by using MMSE and analyzed using Fisher Exact Test with ?=0,05. The result of this research showed that there was difference of dementia level between before and after consuming red apple to experiment and control group. Furthermore, the Fisher Exact Test obtained the value of ?= 0,018 showing that H0 was rejected, means there was influence of red apple consumption to elder changes of dementia level at Wonokromo RT 05 RW 03.  The research concluded that red apple could change the levelt of dementia. Hence, diagnosed as dementia should consume red apple regularly and health worker could give health education about the benefit of red apple to dementia.